2021
DOI: 10.1007/s10755-021-09561-x
|View full text |Cite
|
Sign up to set email alerts
|

Universities and the COVID-19 Pandemic: Comparing Views about How to Address the Financial Impact

Abstract: Universities were forced to move instruction online and send residential students home due to the pandemic, resulting in financial shortfalls. Governing boards, administrators, and governments made decisions including eliminating faculty and staff, and programs yet these decisions were rarely inclusive of university stakeholders or innovative. This study’s purpose is to examine and compare viewpoints of stakeholders in relation to addressing the financial impact of the pandemic in hopes of capturing innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, similar to the disruption caused within K-12 schools, the higher education community saw widespread disruptions in its day-to-day activities due to the high spread of the COVID-19 virus. As a result, the pandemic forced higher education institutions to swiftly implement various institutional changes such as a move to online learning (Al-Areibi et al, 2022) and asking students to leave on-campus housing to decrease the spread of the virus within the university's community (Ramlo, 2021). In this way, educational leaders within higher education institutions, just like the principals in the present study, had to respond quickly to the evolving COVID-19 pandemic to ensure the continuity of education within their establishments while respecting imposed social isolation and distancing measures (Denisov et al, 2021).…”
Section: Discussion Of Findings: Contribution To Higher Education Lea...mentioning
confidence: 99%
“…However, similar to the disruption caused within K-12 schools, the higher education community saw widespread disruptions in its day-to-day activities due to the high spread of the COVID-19 virus. As a result, the pandemic forced higher education institutions to swiftly implement various institutional changes such as a move to online learning (Al-Areibi et al, 2022) and asking students to leave on-campus housing to decrease the spread of the virus within the university's community (Ramlo, 2021). In this way, educational leaders within higher education institutions, just like the principals in the present study, had to respond quickly to the evolving COVID-19 pandemic to ensure the continuity of education within their establishments while respecting imposed social isolation and distancing measures (Denisov et al, 2021).…”
Section: Discussion Of Findings: Contribution To Higher Education Lea...mentioning
confidence: 99%
“…129-130) CJEAP, 200 Gigliotti (2019) concluded that shared governance is an advantage and not an impediment for post-secondary institutions. Referring to the COVID-19 pandemic, Ramlo (2021) argued that shared governance has an important place in crisis management and suggested that it contributes to adaptation, innovation, and improved performance. Similar benefits have been observed with shared leadership.…”
Section: Leadership In a Crisismentioning
confidence: 99%